Lead content of moss collected along the riverbanks of Dasmariñas River. - Cernitchez, Mary Grace S. (2014)
The Dasmarinas River is located along the Aguinaldo Highway where some of its tributaries are located to industrial areas. It is therefore more or less exposed to industrial wastes such as lead. The waters or the Dasmarinas had been subjected to some biochemical tests to determine its quality. In this study, the researchers tested if mosses can indicate the presence of lead in water. Through the use of Flame Atomic Absorption Spectrophotometry, the researchers measured the amount of lead present in the upstream and downstream of the river. One Factor- Analysis of Variance and Two-way Analysis of Variance were used as a statistical method to compare the amount of lead present considering the three replicate samples that are collected in each of the sites. The statistical analysis showed that there is a significant difference in the amount of lead present in upstream and downstream of the Dasmarinas River. Mosses, therefore can be used as bioindicators of lead in water.